Prototype of Laboratory-Scale Plasma Arc for Thin Film Growth and Its Testing - Marta, Akbar Andika; Buwono, Haris Puspito; Yudiyanto, Eko; Rohman, Fatkhur; Weddakarti, Eva (Jurnal Polimesin, 2024)
Thin films, characterized by small-dimensional materials on a substrate formed through sequential deposition of ionic/molecular/atomic materials, have gained significance in various industries. An emerging method, Arc Plasma Deposition (APD), is gaining attention for its effectiveness in minimizing environmental pollution. This research explores the potential of APD, an environmentally friendly technique, in coating materials, particularly copper, at a laboratory scale. The objective is to introduce a cost-effective solution for material deposition, addressing the industrial need for efficient and eco-friendly coating processes. A laboratory-scale prototype for coating materials, specifically utilizing copper metal, is introduced and tested. The APD process is conducted in an atmospheric free-oxygen chamber, where plasma is generated. The deposited copper is analyzed concerning the deposition time, providing insights into the efficiency of the APD technique. The laboratory-scale prototype demonstrates the feasibility of using APD for coating materials. The results indicate the potential of APD in efficiently producing thin films, making it a promising alternative for industrial applications.